Optical and magneto-optical properties of FeₓGa₁₋ₓBO₃ crystals - Edelman, I.; Malakhovskii, A.; Sokolov, A.; Sukhachev, A.; Zabluda, V.; Yagupov, S.; Strugatsky, M.; Postivey, N.; Seleznyova, K. (Functional Materials, 2012)
The single crystals of FeₓGa₁₋ₓBO₃ with 0 < x < 1 have been synthesized by solutionmelt method. Optical absorption spectra demonstrate substantial changes in the region of the strong absorption band edge depending on Fe concentration. This is explained, preferably, by Fe-Fe charge transfer transition processes. Magnetic circular dichroism spectrum in the region of ⁶A₁g —> ⁴Eg, ⁴A₁g d-d transitions and its temperature dependence were measured in the crystal containing 67 % of Fe for the first time.